IMPLICATIONS OF THE SANCTIONS OF CAPTURE FOR CHILDREN SEXUAL CRIMES - Yusep Mulyana (International Journal of Social Science, 2022)
The regulation for chemical castration is contained in Law Number 17 of 2016 concerning Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection. Chemical castration sanctions through a long process are listed in article 81, article 82 and article 81A of Law Number 1 of 2016 as an additional punishment and it can be an option for law enforcement officers, especially judges as judges in the trial to give punishments with the aim of deterrence For the perpetrators, chemical castration sanctions are considered in accordance with the purpose of punishment. Criminal sanctions are one of the methods used to achieve the purpose of holding criminal penalties. The application of the castration penalty has not yet been implemented.